The impact of early adversity on later life health, lifestyle, and cognition - Morgane Künzi; D. A. Gheorghe; J. Gallacher; S. Bauermeister (BMC, 2024)
Abstract Background Early life adversity has been shown to have long-lasting detrimental effects on a variety of biopsychosocial outcomes. Early adversity and its consequences may directly or indirectly affect cognitive aging and increase the risk of developing dementia in older age. Investigating the biopsychosocial outcomes associated with early adverse experiences is essential to inform health policies and promote healthy cognitive development across the life course. Methods The aim of this study is to investigate the effect of early adversity (i.e., abuse and deprivation) on selected outcomes (i.e., physical and mental health, lifestyle, and cognition) in two UK cohorts (the English Longitudinal Study of Ageing (ELSA), N = 12,653, Mdn age = 66, SD age = 9.58; UK Biobank, N = 502,360, Mdn age = 58, SD age = 8.09). In both cohorts, adversities were self-reported retrospectively, and only those adversity types assessed in both cohorts were utilized. A post-hoc analysis was performed to examine the role of education as a mediator of the association between early adversity and the selected outcomes. Results Most of the results show that early adversity is negatively associated with health (both physical and mental), lifestyle, and cognition while also highlighting the important mediating role of education. However, differences exist according to the specific adversity experienced and the cohort studied. Conclusions The results found bring into attention the complex associations between early adversity and multiple later life outcomes, and suggest that various mechanisms might be at play. Furthermore, the findings highlight the importance of multi-cohort comparisons for the generalization of the results.